ANALISIS RISIKO PRODUKSI USAHATANI PADI ORGANIK DI DESA ROWOSARI KECAMATAN SUMBERJAMBE KABUPATEN JEMBER - Julita Hasanah; Muhammad Rondhi; Triana Dewi Hapsari (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2018)
Government began to apply the concept of organic farming in order to maintain the sustainability of agriculture. Organic farming is applied to the organic rice farming of Jember Regency. This kind of farming have some risks. The prominent risk in organic rice farming is production. Research conducted at rowosari village aims to know: (1) The amount of production risk overall; (2) The amount of production risk that seen from the length of application organic farming and land area. The location of research in Rowosari, Sumbejambe which was determined intentionally (Purposive Method). The sampling method was total sampling method. The data that used in study were primary and secondary data. The analyze method used was standard deviation (V) and coefficient of variation (CV). The results of the study showed that: (1) Overall risk of production of organic rice farming in Rowosari Village amounted to 468.25 kg or 10.1% of the average production: (2) The risk of production of organic rice farming in Rowosari Village are based on the land area small (0.5 Ha), medium (0,5-2 Ha) and large (> 2 Ha) respectively 17,6%, 6,3% and 1.3% of the average production. The risk of production of organic rice farming in Rowosari Village is based on the period of implementation from 2015 and 2012, respectively 12.1% and 7.8% of the average production. It showed that the period of organic farming implementation will influence the amount of risk production.